Peningkatan Kompetensi dan Perilaku Hijau Mahasiswa Melalui Pembelajaran Green Pedagogy - Resma Wahyuni; Firdaus L.N; Riki Apriyandi Putra (Journal on Education, 2023)
Education is a process of transferring knowledge as well as the realization of changes in good behavior in students.Green pedagogy (green pedagogy) is present as one of the Education courses in the biology education study program, FKIP, University of Riau. This course provides green education for students to be able to have critical reasoning on various environmental problems that occur at the national to global level. So that various perspectives will produce new solutions to overcome existing problems. This study aims to examine how to increase green competence and behavior of students who have participated in green pedagogy learning. This type of research is descriptive quantitative where the data used is primary data through distributing questionnaires. Based on the results of the research, it is known that there is an increase in the knowledge, attitudes, motivation, and green skills of students participating in green pedagogy learning. This course is also highly recommended to be followed by all biology education students.